Equivalent experimental study on rock breaking of SC-CO2 and industrial emulsion explosive - Nan JIANG; Yingkang YAO; Bin ZHU; Xuedong LUO (工程科学学报)
Supercritical (SC)-CO2 rock breaking technology offers a safe alternative to industrial explosive blasting. Quantitatively calculating the rock breaking efficiency of SC-CO2 is crucial for comparing its engineering application and economic benefits against nonexplosive rock breaking methods. By employing the blasting equivalent theory and field blasting test methods, the equivalence of industrial emulsion explosives was calculated through an engineering analogy. Granite and mudstone sites were selected as blasting tests, and a field test scheme was designed to compare the rock-breaking effects of SC-CO2 and industrial explosives. Using test data of strain, vibration, and rock breaking volume from equivalent field tests, the characteristics and parameters of the rock breaking area, such as volume, shape, bulk rate, and unit consumption of SC-CO2 and industrial explosives in granite and mudstone sites, were compared and analyzed. The analysis of rock-breaking volume and morphology shows that in granite and mudstone sites, larger rock-breaking volumes from SC-CO2 result in long and short axes of the breaking range. As the thickness of the shear slice increases, the carbon dioxide unit consumption rapidly decreases at the mudstone site, whereas changes in unit consumption are less obvious than at the granite site. The carbon dioxide unit consumption is 6–11 times higher than that of explosives. SC-CO2 rock breaking technology has a high bulk rate, while explosive stress waves are more evenly distributed, resulting in a low bulk rate. Consequently, the bulk rate of dynamite blasting is less than that of SC-CO2 rock breaking. The surface vibration velocity of SC-CO2 rock breaking is considerably lower than that of industrial explosive rock breaking. The combined vibration velocity at industrial explosive blasting points is 9–11 times higher than at SC-CO2 rock breaking points. SC-CO2 rock breaking has little effect on the surrounding environment vibrations. The peak combined stress at the SC-CO2 rock breaking point is higher than that of industrial explosive rock breaking. In the SC-CO2 rock-breaking test, the combined stress at each measuring point is 1.2–1.6 times that of the corresponding point in the explosive rock breaking test. Industrial explosives blasting generates more intense shock waves, but the SC-CO2 method produces a higher peak combined stress because the high-pressure gas from SC-CO2 rock breaking creates a gas wedge effect. Owing to site constraints, field tests were carried out only at two sites, granite and mudstone. Additional rock bodies should be tested to generalize the conclusions.